Biomimicry : Inventions inspired by nature - Lee, Dora, 1968-; Thompson, Margot, 1965- (Toronto : Kids Can Press, 2011)
Contains descriptions of technological innovations inspired by things found in the natural world.
Learning from Mother Nature -- Nature thought of it first -- Why should we copy nature? -- Shaped for survival -- Smart structures -- Magic materials -- Creative communications -- Medical marvels -- On the move -- Designs that work -- Pollution-free power -- Dealing with the tough stuff -- Computing, nature's way -- Machines that move like animals ... -- ... and think like humans -- Nature's nanotechnology -- Sustaining our future -- Nature, the teacher.
"The artwork in this book was rendered in acrylic on canvas"--Title page verso.
Includes index.
1110
Outstanding Science Trade Books for Students K-12, 2012
Keywords: Biomimicry -- Juvenile literature; Technological innovations -- Juvenile literature; Biomimicry; Technological innovations; Bionique -- Ouvrages pour la jeunesse; Innovations -- Ouvrages pour la jeunesse; Engineering; Technological innovations